Analysis of Financial Literacy and Financial Behavior Towards Investment Decisions: Case Study on Kartu Indonesia Pintar at University State of Makassar - Pratiwi Musa, Kartika Septiary (Abadi Institute, 2025)
Every investment has consequences, so choosing wisely is crucial as it will impact the future. Greater accessibility to financial services and products for the general public may not always yield positive results, especially for younger generations who lack good financial management skills. The aim of this study is to examine how financial behavior and financial literacy influence the investment choices made by KIP recipient students at Universitas Negeri Makassar from the 2022 cohort. Using a quantitative technique, 100 respondents were given questionnaires as part of the research methodology. Multiple regression analysis and validity tests were employed in the data analysis, which was conducted using SPSS software version 30.0.0. The results of the study indicate a substantial positive correlation between investing decisions and financial literacy, with higher levels of financial literacy being associated with better investment decisions. Furthermore, it was found that students' investment decisions are significantly influenced by their financial behavior